2021
DOI: 10.3390/ijms22158033
|View full text |Cite
|
Sign up to set email alerts
|

Non-Covalent Forces in Naphthazarin—Cooperativity or Competition in the Light of Theoretical Approaches

Abstract: Non-covalent interactions responsible for molecular features and self-assembly in Naphthazarin C polymorph were investigated on the basis of diverse theoretical approaches: Density Functional Theory (DFT), Diffusion Quantum Monte Carlo (DQMC), Symmetry-Adapted Perturbation Theory (SAPT) and Car-Parrinello Molecular Dynamics (CPMD). The proton reaction paths in the intramolecular hydrogen bridges were studied. Two potential energy minima were found indicating that the proton transfer phenomena occur in the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 96 publications
2
10
0
Order By: Relevance
“…This is also true for the gas phase trajectory of 2 . These results are in agreement with the data for naphthazarin [ 61 ]: it was shown that when an asynchronous proton jump occurs, it is very probable that a second proton transfer will follow within a few O-H oscillation periods. From this point of view, it is interesting to note that the solid state simulation of 2 , where the protons are more delocalized, also exhibits important motion correlations.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is also true for the gas phase trajectory of 2 . These results are in agreement with the data for naphthazarin [ 61 ]: it was shown that when an asynchronous proton jump occurs, it is very probable that a second proton transfer will follow within a few O-H oscillation periods. From this point of view, it is interesting to note that the solid state simulation of 2 , where the protons are more delocalized, also exhibits important motion correlations.…”
Section: Resultssupporting
confidence: 92%
“…This shows that from a thermodynamic point of view the molecular forms are preferred, but not strongly, over the PT forms. The trans forms through which the double-proton transfer proceeds [ 61 ] are even higher in energy, e.g., for 1 the differences with respect to the molecular forms are: 5.30/4.65 kcal/mol (B3LYP), 2.82/1.26 kcal/mol (PBE) and 6.81/6.23 kcal/mol ( B97XD). However, these values are all well within the range thermally accessible to the extended molecules at room temperature, especially when the effects of donor–acceptor distance modulation are accounted for (see the Car–Parrinello study below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any PT event is recorded in both bridges at the same time. Our earlier study on naphthazarin [ 39 ] has shown that this process is not ideally synchronous, but the delay between the PT events in the two bridges is only a few OH stretching periods, less than 0.1 ps. The current study shows the same behavior of correlated, but not ideally synchronous, proton motions in the two bridges of a given molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of hydrogen bonds was investigated experimentally and theoretically, see, e.g., Refs. [ 37 , 38 , 39 ]. The presence of this kind of bonding introduces non-covalent interactions into the molecule.…”
Section: Introductionmentioning
confidence: 99%